INDOOR AIR QUALITY STUDY ON COASTAL BAILEO IN WEST SERAM, MALUKU - Purnama Esa Dora Tedjokoesoemo; Felicia Jane Thendean (DIMENSI (Journal of Architecture and Built Environment), 2020)
Thermal comfort is one of the most influencing aspects to affect comfort level in interior. Indoor Air Quality (IAQ) is one part of thermal comfort parametric often suggested in any building assessment for its role to affect health and comfort. IAQ is influenced by physical factors (temperature, air humidity and air velocity) and chemical factors (in the form of substances in the air). Traditional buildings in Indonesia, has long since consider IAQ in its passive design approach, one of them is in Baileo. This paper reports an investigation of IAQ in coastal Baileo in West Seram, Maluku. This quantitative research is conducted in method comparative analysis method. This paper discusses the relation between IAQ in Baileo to building formation and materials selection. The measurement done show that IAQ in coastal Baileo in West Seram has good performance on both physical and chemical factors.